A Case of Sarcoid Uveitis Diagnosed With Mammography Two Months After Normal Chest Imaging - Madison Riccardi; Robert Contento; Cory Christensen; Amy Brady; Rebecca L. Swan; Robert T. Swan (Case Reports in Ophthalmological Medicine)
Conclusions and Importance: The diagnosis of sarcoidosis can be challenging due to nonspecific ocular signs and the potential for falsely negative findings on imaging. This case highlights the importance of patient education and self-surveillance regarding the characteristic systemic symptoms of sarcoidosis, which commonly involve the lungs, eyes, skin, joints, etc. Our report demonstrates the significance of maintaining a high level of suspicion for sarcoidosis in patients with characteristic ocular findings, even when initial imaging results are negative or inconclusive.